Influence of ABCB1 Gene Polymorphism on Rivaroxaban Blood Concentration and Hemorrhagic Events in Patients With Atrial Fibrillation - Yan Wang; Yan Wang; Min Chen; Min Chen; Hui Chen; Fang Wang; Fang Wang (Frontiers Media S.A., 2021)
Background and Objectives: Genetic data on the pharmacokinetics of rivaroxaban and identification of factors that affect its biotransformation, distribution, and excretion will allow for generation of algorithms for personalized use of this drug in patients with atrial fibrillation (AF). Here we tested the effects of ABCB1 (ATP-binding cassette subfamily B member 1) polymorphisms on the valley rivaroxaban blood concentration and on the frequency of hemorrhagic events in patients with AF and propose a personal anticoagulation therapy management protocol.Patients and Methods: This is a retrospective study. We enrolled Mongolian descent patients who met the criteria from May 2018 to August 2019 in Beijing and Fujian. Clinical data on gender, height, weight, liver and kidney functions, drug trough concentration, and drug dosage were collected; we recorded the bleeding events until 6 months after initiating the medication. ABCB1 single nucleotide polymorphisms including rs1128503, rs1045642, and rs4148738 were identified. After reaching the steady state of plasma concentration, the peripheral blood was collected to detect the trough rivaroxaban plasma concentrations before the next medication.Results: We included 155 patients in this study including 81 men and 74 women, with an average age of 71.98 ± 10.72 years. The distribution of ABCB1 genotypes conformed to the Hardy-Weinberg equilibrium. Multiple comparisons between wild (TT) and mutant (CT and CC) genotypes at the rs1045642 locus showed no significant differences of rivaroxaban trough concentrations (TT vs. CT, p = 0.586; TT vs. CC, p = 0.802; and CT vs. CC, p = 0.702). Multiple comparison between wild (TT) and mutant (CC) genotypes at the rs1128503 locus revealed a significant difference of rivaroxaban trough concentrations (TT vs. CC, p = 0.0421). But wild (TT) vs mutant (CT) genotypes and mutant CT vs mutant CC genotypes at the rs1128503 locus showed no significant differences of rivaroxaban trough concentrations (TT vs. CT, p = 0.0651; TT vs. CT, p = 0.6127). Multiple comparisons between wild (GG) and mutant (AG and AA) genotypes at the rs4148738 locus showed no significant differences of rivaroxaban trough concentrations (GG vs. AG, p = 0.341; GG vs. AA, p = 0.612; AG vs. AA, p = 0.649). There was no significant correlation between ABCB1 gene variation loci rs1045642, rs1128503, rs4148738 and bleeding events.Conclusion: rs1128503 locus variations are correlated with the serum concentration of rivaroxaban in patients of Mongolian descent. But no significant correlation between rs1128503 locus variations and bleeding events were obtained.